Declining trends in birth prevalence and severity of singletons with cerebral palsy of prenatal or perinatal origin in Australia: A population‐based observational study. (8th March 2022) - Smithers‐Sheedy, Hayley; Waight, Emma; Goldsmith, Shona; Reid, Sue; Gibson, Catherine; Watson, Linda; Auld, Megan; Badawi, Nadia; Webb, Annabel; Diviney, Leanne; Mcintyre, Sarah; ,
Abstract : Aim: To investigate temporal trends in birth prevalence, disability severity, and motor type for singletons with prenatal or perinatally acquired cerebral palsy (CP). Method: Numerator data, number of children with CP born a singleton between 1995 and 2014, confirmed at 5 years of age, were drawn from three state registers with population‐level ascertainment. Birth prevalence estimates and 95% confidence intervals (CI) were calculated per 1000 singleton live births for the three states combined, overall, by gestational age group, by dichotomized disability severity, and spastic laterality. Poisson regression models were used to analyse trends. Using data from all eight registers, trends in the proportional distribution of CP subtypes overall and stratified by gestational age were examined. Results: Birth prevalence of CP declined from 1.8 (95% CI 1.6–2.0) in 1995 to 1996 to 1.2 (95% CI 1.1–1.4) in 2013 to 2014 (average 5% per 2‐year epoch, p <  0.001). Declines in birth prevalence were observed across all gestational age groups with the largest decline in children born at <28 weeks (average 8% per epoch, p <  0.001). Prevalence of moderate‐severe disability declined for children born at <28 and ≥37 weeks (average 11% and 7% per epoch respectively, p  < 0.001). The proportions of bilateral spastic CP declined ( p  < 0.001) at <28 weeks ( p =  0.014) and ≥37 weeks ( p  < 0.001). The proportion of children with dyskinesia increased (28–31 weeks: p  = 0.021, 32–36 weeks: p  = 0.001, and ≥37 weeks: p  < 0.001). Interpretation: Birth prevalence of CP and moderate‐severe disability (<28 and ≥37 weeks) declined in Australian singletons between 1995 and 2014, reflecting changes in prenatal and perinatal care over time. What this paper adds: Declines in birth prevalence of prenatal or perinatally acquired cerebral palsy were observed for singletons born in Australia between 1995 and 2014. These declines were evident across all gestational age groups. Declines in birth prevalence of moderate‐severe disability were observed for children born at <28 weeks and ≥37 weeks. What this paper adds: Declines in birth prevalence of prenatal or perinatally acquired cerebral palsy were observed for singletons born in Australia between 1995 and 2014. These declines were evident across all gestational age groups. Declines in birth prevalence of moderate‐severe disability were observed for children born at <28 weeks and ≥37 weeks. This original article is commented on by Villamor on pages 1054–1055 of this issue.